A CASE OF DELAYED PUBERTY AND ANOSMIA - L, Yee Lin; Y, Fabian (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION A 26-year-old lady presented at the age of 13 years with delayed puberty and faltering growth. She had a past history of left eye squint surgery for underlying optic disc coloboma, but was otherwise systemically well. She was found to have absent sense of smell. There were no prior feeding problems and she had normal intelligence. Initial assessment revealed a proportionately smallsized girl who was prepubertal, there were no obvious dysmorphic features. CASE Her karyotype was 46XX. Her bone age was 8 years at chronological age of 13 years. A combined pituitary function test showed poor LH and FSH response with peak responses of 0.34 IU/L and 2.62 IU/L respectively. Serum estradiol was <37 pmol/L. GH, TSH and cortisol responses were normal. MRI of the pituitary was normal. The findings of isolated hypogonadotropic hypogonadism with anosmia pointed to a clinical diagnosis of Kallmann syndrome. She was commenced on hormonal replacement therapy for induction of puberty. She complained of hearing difficulties at the age of 19 years. Pure tone audiometry confirmed bilateral conductive hearing loss. Subsequent CT temporal bones showed bilateral absence of all the semi-circular canals. The clinical diagnosis was revisited and revised to possible CHARGE syndrome as the patient fulfilled 3 major criteria of CHARGE syndrome i.e. coloboma, anosmia and absent semi-circular canals and 1 minor criterion i.e. delayed puberty secondary to hypogonadotropic hypogonadism. This was confirmed by a detectable pathogenic CHD 7 gene mutation. CONCLUSION The presence of non-reproductive anomalies including anosmia, coloboma and hearing defects, are red flag indicators of an underlying congenital hypogonadism. CHARGE syndrome is a major differential diagnosis of Kallmann syndrome and should be considered especially in girls. Patients with anosmia and hypogonadotropic hypogonadism should be screened for clinical features consistent with CHARGE syndrome.